Influence of intra-ensemble energy transfer on the properties of nanocrystal quantum dot structures and devices - Gounko, Iouri; Bradley, Louise (My University, 2010)
The impact of intra-ensemble Forster resonant energy transfer (FRET) on the optical properties of monodispersed quantum dot (QD) monolayers and a donor/acceptor FRET bilayer structure are presented. The QD structures are characterized by steady-state absorption and photoluminescence (PL) spectroscopy as well as time-resolved PL measurements. The optical properties of the monodispersed monolayers, such as peak emission wavelength and PL decays, are strongly influenced by FRET from smaller to larger QDs within the ensemble. Comparing several QD samples, the spectral overlap of the QD ensemble and the QD concentration were identified as parameters that allow for tuning of FRET in monodispersed QD structures. For the donor/acceptor QD bilayer structure an unexpected decrease of the FRET efficiency between donor and acceptor layers is observed with increasing donor QD concentration. The concentration-dependent donor lifetime and a constant donor-acceptor FRET rate can explain this decrease within the FRET rate model. Even though the donor-acceptor FRET rate is donor-concentration independent - as expected from theory - its competition with donor-donor energy transfer leads to a concentration dependence of the FRET efficiency from donors to acceptors. This shows that intra-ensemble FRET can have an important impact on device performance.
12th International Conference on Transparent Optical Networks (ICTON), 2010
PUBLISHED
Munich
Keywords: Optics; monolayers; nanostructured materials; Nanoscience & Materials